Rhythm in the Poem Al-Burda by Tamim Al-Barghouti: An Analytical Study - Suzan Ahmed Khudhur; Srood Kanaan Shakir (Zanco Journal of Humanity Sciences)
Rhythm is one of the basic elements of Arabic Poetry as well as the main Components of the construction of Poetry. In this respect, rhythm will give its own identity and differes from the other parts of speech. In fact, its the main source of life deep inside, The construction of poetry. By So doing, it will give its meaning Sweetness and acceptance in hearing.